PENGEMBANGAN MODEL ASESMEN OTENTIK DALAM PEMBELAJARAN KETERAMPILAN BERBAHASA INDONESIA LISAN DI SEKOLAH MENENGAH ATAS (SMA) - Sri Wahyuni (LITERA, 2010)
This study aims to develop a model of authentic assessment in the learning of the spoken Indonesian language skill in senior high schools. The model was adapte  from the Reflective, Recursive Design and Development (R2D2) model by Willis and the model of spoken language assessment by O’Malley Pierce. The product of the development is a set of authentic assessment in the spoken Indonesian language skill in senior high schools, consisting of (a) assessment planning, (b) assessment mapping, (c) assessment instrument and rubric, (d) evaluation standard, and (e) score interpretation. The product is equipped with a VCD containing the implementation model to help teachers conduct authentic assessment. In general, the developed authentic assessment model is effective to evaluate the spoken Indonesian languageskill in senior high schools.